The Journey of Natural Products: From Isolation Stage to Drug’s Approval in Clinical Trials - Yehezkiel Steven Kurniawan; Tantiana Indriani; Hanif Amrulloh; Langit Cahya Adi; Arif Cahyo Imawan; Krisfian Tata Aneka Priyangga; Ervan Yudha (Pandawa Institute, 2023)
Nature serves as an excellent inspiration for researchers in the fields of chemistry and medicine. Terrestrial or marine organisms produce billions of natural products with unique chemical and physical properties. Some of them have been used in traditional therapy for specific diseases since ancient times. Although their exact chemical structures have yet to be elucidated clearly in that time, investigations in medicinal chemistry have been well documented. Furthermore, utilizing natural products in drug design and development offers advantages such as high biocompatibility, low toxicity, fewer side effects, wide bioactivities, and large structure diversity. Nowadays, rational drug research using computer-aided drug design is well established to cut the long way of drug discovery and overcome the resistance cases and the increment in the number of active patients. This review will highlight some natural products to comprehensively understand their journey from unknown natural products, isolation, purification, characterization, in silico evaluation, bioactivity screening assay, drug modifications, in vitro investigation, in vivo examination, and clinical trial.